Scanning Electron Microscopic studies on culm And Leaf Epidermis of Indian Bamboos - Bisen, S. S.; Mishra, G. P.; Sharm, S. C. (Indian Forester, 1988)
This study was taken up mainly for evaluation of the importance of epidermal features on the culm and leaf of bamboos. Critical analysis of the epidermal features present on the culm and leaf surface from the 36 species belonging to 22 genera either naturally growing or cultivated, show that the epidermal features are very useful in differentisting the genera and their species. The culm epidermis however is not that reliable, due to the variations from bottom to the top of the culm, associated with encrustations masking the details. The leaf epidermal features can be relied upon for identification, of genera and their species, as they show no variations due to age, locality, soil and environmental factors. If this approach is widely tried on the other genera and species growing in China, Japan, Indonesia, Malaysia and South America, the validity of this approach can be furtber tested, which will go a long way in bamboo identification and classification in the absence of flower.